Brazilian Red Propolis—Chemical Composition and Botanical Origin - Daugsch, Andreas (Oxford University Press, 2008)
Propolis contains resinous substances collected by honey bees from various plant sources and has been used as a traditional folk medicine since ca 300 BC. Nowadays, the use of evidence-based complementary and alternative medicine (CAM) is increasing rapidly and so is the use of propolis in order to treat or support the treatment of various diseases. Much attention has been focused on propolis from Populus sp. (Salicaceae) and Baccharis dracunculifolia (Asteracea), but scientific information about the numerous other types of propolis is still sparse. We gathered six samples of red propolis in five states of Northeastern Brazil. The beehives were located near woody perennial shrubs along the sea and river shores. The bees were observed to collect red resinous exudates on Dalbergia ecastophyllum (L) Taub. (Leguminosae) to make propolis. The flavonoids of propolis and red resinous exudates were investigated using reversed-phase high-performance liquid chromatography and reversed-phase high-performance thin-layer chromatography. We conclude that the botanical origin of the reddish propolis is D. ecastophyllum. In areas where this source (D. ecastophyllum) was scarce or missing, bees were collecting resinous material from other plants. Propolis, which contained the chemical constituents from the main botanical origin, showed higher antimicrobial activity.